What’s more important for product design – usability or emotionality? An examination of influencing factors - Buker, Tina; Schmitt, Teresa; Miehling, Jörg; Wartzack, Sandro (Journal of Engineering Design, 2022)
Usability and emotionality are fundamental aspects of user experience. However, the actual creation of an equally usable and emotionally appealing product design is still challenging for product developers, not least because of competing objectives during such equal consideration of both aspects. In order to make a user-oriented decision between a more usable or more emotional product design, product developers need a profound understanding of what matters to the user in different usage situations. By conducting 22 semistructured interviews, we contribute to this aim by identifying and examining factors that influence a user’s perceived importance of usability and emotionality in product design. In total, 29 influencing factors were identified with the purpose of use, the type of product and other people’s attitudes towards a product being most relevant or both emotionality and usability. Nine influencing factors from the literature were additionally examined in terms of their strength and direction in which they influence the importance of emotionality and usability. Hereby, considerable differences within individual expressions of the influencing factors were revealed. Furthermore, the perceived importance of emotionality varied much more than that of usability.<br
Keywords: Usability; emotional design; user experience; user-centred design; interview